Development model and optimization path of Guizhou modern mountainous high-efficiency agricultural industrial chain—a case study of vegetable industry. Issue 7 (March 2020) - An, Dan; Zhou, Zhongfa; Yan, Lihui; Zhu, Changli; Zhao, Xin
Abstract: In order to understand the present situation and future development direction of the large ecological industrial chain. Taking the vegetable industry in Guizhou as an example, this article analyzes the development status, model, structure, and existing problems of the vegetable industry chain based on the development of "ecological utilization" industries, and proposes a reasonable and effective optimization path for the development of future ecological industries. The results showed that although the vegetable industry in Guizhou Province is widely distributed and has stable development, there are problems such as a short industrial chain, low brand building and publicity, infrastructure construction, and the need to improve the government's institutional protection; It is recommended to optimize the development of ecological agriculture by innovating the industrial chain model, optimizing the layout, and integrating multichannel publicity to create distinctive industrial product brands, strengthen facility construction and policy guarantee mechanisms, explore ways to realize the value of ecological products, and form a competitive and orderly ecological product market system. Based on the analysis of the development of Guizhou Province 's modern mountainous and highly efficient agricultural industry chain, the development model and existing problems of Guizhou's mountainous and highly efficient agricultural industry chain are clarified. From the perspective of regional development, relevant suggestions are put forward for modern mountainous and highly efficient agriculture and even for promotion Provide theoretical basis for the implementation of ecological civilization.